School health program: the interface education/health and drug use (Research, Society and Development, 2020)
The objective of this work is to analyze the actions of the PSE (Programa Saúde na Escola or School Health Program), regarding the prevention of alcohol, tobacco, crack and other narcotics consume. This is a qualitative, exploratory, descriptive, comprehensive study with high school students and teachers at a public school in São Luís - Maranhão, from January to June 2017. The teachers reported knowing the PSE superficially, affirming that they did not participate of its programming or in the implementation of the proposed interventions. They also associated the program's activities with dental and assistentialist operations. The students, when asked about what they yearn for themselves and for society, respect, family life and world peace stood out. They exposed violence, crime and unemployment as difficulties. The data provided indicators on the student’s everyday life and the education developed at school, which can be used for thoughts and planning the PSE work. Although this school has internally established an intersectoral working group between teachers and health professionals, the responsibility for implementing the planning was left to the health sector and professionals of the Basic Unit to which the school is linked.